In situ SAXS studies of the pore development in biochar during gasification - Liu, Y.; Paskevicius, Mark; Sofianos, M.V.; Parkinson, G.; Li, Chun-Zhu (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
This work investigates the pore development in biochar during gasification using synchrotron small angle X-ray scattering (SAXS) as an in situ characterization technique. The influence of the gasifying agents (H2O, CO2 or H2O/CO2) and temperature on the pore structure development in biochar was studied by carrying out the hour-long gasification of mallee wood biochar (106–250 μm) in: (i) H2O at 700, 800 and 900 °C respectively, (ii) CO2 at 700 and 800 °C, and (iii) a mixture of H2O and CO2 (H2O/CO2) at 800 °C. There was a minor increase in the micro- and mesopore volumes in biochar during gasification in H2O at 700 °C, in contrast to CO2 gasification at the same temperature where no measurable changes to the pore structure were observed. At 800 °C, biochar derived from H2O/CO2 gasification exhibited the highest specific surface area (SSA). CO2 tended to produce a highly microporous biochar with a mesopore network showing pore fractal features. Micropore enlargement was a major process in the presence of H2O. In this case, the pore structure evolved from being a porous network of branched micropore clusters (pore fractal) to being dominated by rough surfaced mesopores (surface fractal) during gasification in H2O and H2O/CO2. The evolution of pore structures result from the different ways in which carbon atoms were removed by either H2O or CO2. H2O is more reactive and less selective towards reacting with biochar, resulting in a less worm-like network of pores than CO2. Moreover, it was found that increasing temperatures can lead to faster rates of pore generation and pore enlargement, which is attributed to the increased reaction rate and the less selective removal of carbon atoms.